The effect of some shoulder girdle muscles fatigue after a resistance training session and a volleyball training session on scapular resting position and scapulohumeral rhythm ratio - Hosseinimehr, S. H.; Anbarian, M. (Research in Medicine, 2020)
Background and Aims: previous studies have stated shoulder muscle fatigue directly effects on scapula and humerus motions. Hence, kinematics of the shoulder joint depend largely on the muscles around it .The purpose of this study was to investigate the effect of some shoulder girdle muscles fatigue after a resistance training session and a volleyball training session on scapular resting position and scapulohumeral rhythm ratio in volleyball players. Materials and Methods: in a semi experimental study thirty male volleyball players selected as statistical sample randomly. The fatigue protocol consisted of a resistance training session (front and back barbell shoulder press, wide grip lat pull-down, machine shoulder press, and chin up) and a volleyball training session. Two inclinometers were used to measure humeral abduction and scapular up or dawn ward rotation in scapular resting position, 45°, 90° and 135° shoulder abduction in frontal plane. Subject performed humeral abduction with dominant shoulder in frontal plane. Scapulohumeral rhythm ratio was calculated from division humeral abduction to upward rotation of the scapula from scapular resting position to 45°, 90°, 135°, from 45° to 90° and from 90° to 135° humeral abduction in frontal plane. In the first session, scapular kinematic measurements performed and then one of the fatigue protocols performed randomly and finally scapular kinematic measurements performed again. In second session other fatigue protocol performed. Paired sample test was used for determination of significant differences between pretest and posttest. The level of significance was set at a< 0.05. Results: results showed shoulder girdle muscles fatigue after a volleyball training session has no significant effect on scapular resting position and scapulohumeral rhythm ratio (p=0.14), also shoulder girdle muscles fatigue after a resistance training session has no significant effect on scapular resting position but it has significant effect on scapulohumeral rhythm ratio in 135° shoulder abduction (p=0.03). Conclusion: it seems excessive shoulder girdle muscles fatigue can make scapulohumeral rhythm ratio dysfunction and shoulder disorders.